Efficient total synthesis of iso-cladospolide B and cladospolide B - Pandey, SK; Kumar, P (Tetrahedron Letters, 2005)
An efficient synthesis of iso-cladospolide B and cladospolide B has been achieved using Jacobsen's hydrolytic kinetic resolution (HKR), Sharpless asymmetric dihydroxylation and Yamaguchi macrolactonization as the key steps. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cladospolide B; Hydrolytic kinetic resolution; iso-cladospolide B; sharpless asymmetric dihydroxylation; Yamaguchi macrolactonization